2007
DOI: 10.1136/bjo.2007.118570
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of the sigma agonist Pre-084 in the rat retina

Abstract: Aim: With the rationale that amyloid beta (AB) is toxic to the retina, we here assessed the role of TRAIL, a mediator of AB toxicity and related signal transduction, in a rat model. We also attempted to demonstrate possible protective effects of s1 receptor agonists in these processes. Methods: AB and the s1 receptor agonist Pre-084 were injected intravitreally in the anaesthetised rat. In additional experiments, the s1 receptor antagonist BD1047 was administered to assess specificity of the effects of Pre-084… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…Although SN79 treatment was found to mitigate METH-induced increases in STAT3 phosphorylation, it may be possible that modulation of ERK1/2 and JNK pathways are contributing to increases in SOCS3 (Baker et al 2008), thereby leading to the blockade of STAT3 phosphorylation seen in the current report. Supporting this hypothesis are previous studies showing the modulation of ERK1/2 and JNK signaling by various sigma receptor ligands (Cantarella et al 2007; Nishimura et al 2008; Son and Kwon 2010; Tan et al 2010; Tuerxun et al 2010), although their effects specifically within astrocytes on these signaling pathways are currently unknown.…”
Section: Discussionmentioning
confidence: 77%
“…Although SN79 treatment was found to mitigate METH-induced increases in STAT3 phosphorylation, it may be possible that modulation of ERK1/2 and JNK pathways are contributing to increases in SOCS3 (Baker et al 2008), thereby leading to the blockade of STAT3 phosphorylation seen in the current report. Supporting this hypothesis are previous studies showing the modulation of ERK1/2 and JNK signaling by various sigma receptor ligands (Cantarella et al 2007; Nishimura et al 2008; Son and Kwon 2010; Tan et al 2010; Tuerxun et al 2010), although their effects specifically within astrocytes on these signaling pathways are currently unknown.…”
Section: Discussionmentioning
confidence: 77%
“…As β-amyloid is toxic to the retina, the sigma-1 receptor agonist, PRE-084, was used to examine if it might protect retinas against β-amyloid-induced retinal degeneration. Indeed, PRE-084 was protective i retinal neurons and was effective in abrogating the β-amyloid-induced biochemical changes, including the overexpression of TRAIL and the apoptotic protein, Bax, and the phosphorylation of JNK (Cantarella et al, 2007). Further, the effect of PRE-084 was blocked by BD1047 (Cantarella et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, PRE-084 was protective i retinal neurons and was effective in abrogating the β-amyloid-induced biochemical changes, including the overexpression of TRAIL and the apoptotic protein, Bax, and the phosphorylation of JNK (Cantarella et al, 2007). Further, the effect of PRE-084 was blocked by BD1047 (Cantarella et al, 2007). Another laboratory used primary ganglion cells isolated from rat retinas and found that (+)pentazocine prevented the excitotoxicity to cells (Dun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Topical administration of σR1-site agonists lowers intraocular pressure and might provide control of ocular hypertension (22, 23). Profound retinal neuroprotection has been demonstrated using σR1 ligands in vitro (24-27) and in vivo (28, 29). …”
Section: Introductionmentioning
confidence: 99%